A study on environmental climate and communicative competence among university students in Shandong Province, China - Liu, Jiawen; Chang, Yuan-Cheng (Edelweiss Applied Science and Technology, 2026)
This study examines the relationship between environmental climate and communicative competence among university students in Shandong Province, China. A quantitative research design was adopted to investigate how students’ perceptions of the university environment influence their communication abilities. Data were collected through a structured questionnaire administered to 625 undergraduate students from several universities in Shandong Province. Statistical analyses, including reliability and validity tests, confirmatory factor analysis, correlation analysis, and regression analysis, were conducted to examine the relationships between variables. The results reveal that environmental climate has a significant positive effect on students’ communicative competence (β = .570, p < .001). Students perceiving their university environment as supportive, inclusive, and interactive tend to demonstrate stronger communication abilities. The findings indicate that a positive campus climate plays an important role in fostering students’ interpersonal development in higher education. Universities should focus on creating supportive learning environments, encouraging collaborative learning, and promoting academic and social interaction to enhance students’ communicative competence.